Novel Picobirnaviruses in Respiratory and Alimentary Tracts of Cattle and Monkeys with Large Intra- and Inter-Host Diversity - Patrick C. Y. Woo; Jade L. L. Teng; Ru Bai; Ying Tang; Annette Y. P. Wong; Kenneth S. M. Li; Carol S. F. Lam; Rachel Y. Y. Fan; Susanna K. P. Lau; Kwok-Yung Yuen (Viruses, 2019)
Picobirnaviruses (PBVs) are mostly found in animal alimentary samples. In this study, among 576 respiratory specimens from 476 mammals and 100 chickens, genogroup I PBVs were detected in three cattle and three monkeys, and a genogroup II PBV-positive sample was collected from one cattle specimen. More than one PBV sequence type was observed in two and one genogroup I PBV-positive samples from cattle and monkeys, respectively. Twenty-four complete/near-complete segments 2 (nine from respiratory and 15 from alimentary samples) from the cattle and monkey genogroup I PBVs and one complete segment 2 from the cattle genogroup II PBV were sequenced. Similar to other studies, the cattle PBVs also showed a high diversity. In contrast, the monkey PBVs observed in this study were clustered into three distinct clades. Within each clade, all the sequences showed >99% amino acid identities. This unique phenomenon is probably due to the fact that monkeys in our locality reside in separated troops with minimal inter-troop contact.